MODALITY AND HEDGING UTILIZATION OF REBECCA AHN TO MAINTAIN LANGUAGE POWER IN THE MOVIE: THE BLING RING - AULIA, ALMIRA NOVA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Language Power, Modality, Epistemic Modality, Deontic Modality, DynamicModality, Hedging, Propositional Hedging and Speech Act Hedging. This research described the utilization of modality and hedging expressions by Rebecca Ahn to maintain language power in The Bling Ring movie. Modality and hedging are linguistics features which are useful and possibly be utilized when a person may desire to appear firmly aligned to an idea but wish for limiting how much it may be represented in terms of a firm promise and command. Furthermore, modality and hedging were proven as the factors to maintain language power since both modality and hedging can modify a message to appear just like what a speaker wanted. Qualitative approach is applied in order to describe the linguistic phenomenon holistically. The data is taken from The Bling Ring movie script to obtain the utterances of Rebecca Ahn as the language power holder, and the movie is watched to get the context of the utterance. The data analysis is done with the implementation of coding procedure in order to categorize and describe the findings.On the basis of the findings, it can be concluded that Rebecca Ahn maintains language power by utilizing epistemic modality in delivering the value of deduction and a story told; by deontic modality in giving order and promise, and in committing herself and or her friends to do certain action motivated by certain situation; by dynamic modality in showing her desire toward something, by propositional hedging in modifying spoken ideas; and by speech act hedging in modifying an order into a request to hide the force. Although it is mostly believed that power only can be possessed through social status or position, the utilization of certain linguistic features such as modality and hedging can support a power holder like Rebecca Ahn to control her friends to do particular intended action. Thus, Rebecca Ahn does more effort to utilize the power by demonstrating modality and hedging. It means power is possessed through effort.  Thus, power is noticed when the Rebecca Ahn’s friends perform an action which Rebecca Ahn expects them to do.Finally, the researcher suggests the next researcher to; find a character’s motives of language power utilization in order to gain deeper understanding, and; employ modal logic model proposed by Portner (2009) to get more exact analysis to avoid subjective bias. Meanwhile, The Faculty of Cultural Studies of Universitas Brawijaya can consider this topic to be taught in the Discourse Analysis class to give students the knowledge of applied discourse.